Adverse Effects of Passive Smoking on Executive and Pulmonary Functions in School Aged Children in Egypt - Ahmed S. Mahmoud, Naglaa A. Zaky, Emad A. Mahgoub, Mostafa S. Ali (South Eastern European Journal of Public Health, 2025)
Background: Passive smoking is the leading preventable cause of many issues related to physical and mental health constraints in children. Objectives: This study aims to investigate the effect of passive smoking on executive and pulmonary functions in school-aged children. Methods: An observational (case control) study including 240 school aged children of both sexes (group A includes 120 passive smoking children and group B includes 120 non-passive smoking children), with age ranged from 8-12 years. For both groups, executive functions were evaluated using the Tower of Hanoi, Stroop colored word test, and Trail-making test (A). In addition, pulmonary functions have been investigated through (forced vital capacity (FVC) and forced expiratory volume in one second (FEV1) were measured by the spirometer. Results: There was a significant decrease of executive function tests due to passive smoking (p < 0.001). Also, there was a significant reduction in all measurable pulmonary function tests (FVC and FEV1) in passive smoking children compared with non-passive smoking children (p < 0.001). Conclusion: Passive smoking has an adverse impact on executive and pulmonary functions in school-aged children.